Feminist reflections on social work intervention with women experiencing violence in Bogota - Bueno, Ana Marcela; Buitrago, Maribel Florián; Chinchilla Romero, Diana Milena (Critical Proposals in Social Work, 2021)
The intervention of social work with women who have experienced violence on the part of their peers, in most cases, remains constant across the entire continent, even worldwide. In Colombia, gender violence has been a theme that increasingly takes on greater strength as an acute phenomenon that requires institutional attention, and therefore it has begun to have a relevant place in social policy. In spite of this visibility, this topic continues to be an urgent one to address from the different social spheres, as it is not possible to reduce the numbers of violence and on the other hand, the institutions also have sufficient clarity regarding the requirements of this type of attention, given the limits that are imposed in each case. Based on some investigations on gender-based violence directed and on conversations with social workers in exercise in the scope of attention to women who have been victims of gender-based violence in State institutions in Bogotá, a reflection on the complexities of this phenomenon, of the characteristics of its intervention, as well as of the challenges that it raises its attention in this professional field. Part of the challenges that we identified in this reflexive process are that, as professionals of social work, we have a decisive political role in the transformation of the patriarchal codes of daily exchange with the place where the questioning of sexism is sought, with the active participation of them with it that it achieves in the last ones to conquer spaces and dynamics that revive in its wellbeing and in the claim of its rights.